Penambahan Limbah Padat Kunyit (Curcuma Domestica) pada Ransum Ayam dan Pengaruhnya terhadap Status Darah dan Hepar Ayam - Erniasih, Endah; Saraswati, Tyas Rini (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2006)
Curcuma domestica is the one of materials which is used in traditional medicine. In this research Curcuma domestica solid waste was used as mixture chicken food. The aim of this research was investigated that Curcuma domestica solid waste is untoxic.The animal treatment which was used in this research was day-old chickens. The concentration of Curcuma domestica solid waste contained 0%, 5%, 10%, 15%, 20%. The research was using Complete Randomize Design with not similar replications.The results of this experiment were indicated that there were not changes on weight and hepatocyts diameter.The blood status was not change too. The conclusion of this experiment that added Curcuma domestica solid waste as mixture in the chicken food can be recommended with 10% is the maximum value.